EVALUASI PELAKSANAAN KARTU KUSUKA DI UPT PELAYANAN USAHA PERIKANAN KUNDUR - Ica Trifiwidyana; Nazaki Nazaki; Ryan Anggria Pratama (PT. Jurnal Center Indonesia Publisher, 2024)
The Ministry of Maritime Affairs and Fisheries, in its government mission, carries out the creation of Maritime and Fisheries Business Actor Cards (KUSUKA). This card is an individual identification card issued by the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia for maritime and fisheries business actors in Indonesia. This research discusses matters related to the results of the implementation of the KUSUKA card program services at the Kundur District Fisheries Business Services UPT. The aim of this research is to find out the results of the implementation of the KUSUKA card at the Kundur Fisheries Business Services UPT. The approach used in this research is descriptive qualitative using data collection methods in the form of observation, interviews and documentation. The results of this research show that the implementation of the KUSUKA card program for the community at the Kundur District Fisheries Business Services UPT is as expected. The implementation of this program meets expectations based on the following 6 indicators: a). effectiveness: the results achieved have met expectations. b) Efficiency: time and costs are efficient. c). Adequacy: Human resources and facilities/infrastructure are adequate. d). Alignment: program benefits are adequate. e). Responsiveness: service is adequate. f). Accuracy: the program results are useful. However, the effectiveness indicators and efficient indicators still cannot be said to meet expectations, this is because there are problems or obstacles such as the lack of clarity on the time for printing KUSUKA cards which only adjusts the bank's ability to print cards, the functions and benefits of the program have not been fully felt and there is no real change in the lives of the community or fisheries business actors in the Kundur District Fisheries Business Services UPT. Keywords : Public Services, Evaluation, Kusuka Card